Komparasi Ayat-Ayat Al-Qur’an tentang Zakat Sebagai Media Kegiatan Ekonomi Islam dalam Kajian Tafsir Al Maraghi - Hafid Hafid (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2020)
This article discusses the verses of the Qur'an about Zakat as a media for the activities of the Al-Maraghi Tafsir Islam. The results of the analysis concluded that the function of zakat as a medium of worship for the servants of God who becomes muzakki (paying zakat) to provide benefit for themselves or individuals (nafs) and serves to be an economic driver for the servants of God who are in the environment running the zakat system, then delivering zakat as an instrument that provides a collective benefit (jama'i). Keywords: Zakat verses, Islamic economics, Tafsir al-Maraghi